Metode Penafsiran Ibn Qayyim dalam Tafsîr al-Qur’ân al-Hakîm - fitrian Jalal, Zaglul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2012)
This article is intended as an introduction to the work of heritage interpretation Ibn Qayyim al-Jawzîyah. As an introduction course cannot be expected to complete an exposure. But from the lilte bit of description above, at least we getting conclusion that general methods are applied in interpreting. The Koran is a tahlîlî method or tajzi’. However, if viewed from term of the propensity interpretation it’s can be categorized as a al-ma’thûr interpretation despite as well as the interpretation of bi al-ra’y. As a work of interpretation, al-Qayyim interpretation may be not as famous as the work of other commentators, such as the interpretation of al-Jâmi‘ al-Bayân, Tafsîr Ibn Kathîr, Tafsîr Jalâlayn an so on. But as a work of Muslim intellectuals seem this book need to be reviewed more thoroughly.